B chromosome polymorphism in South American cichlid. Issue 1 (30th November 2018) - Perazzo, Giselle Xavier; Noleto, Rafael Bueno; Vicari, Marcelo Ricardo; Gava, Adriana; Cestari, Marta Margarete
Abstract: Extra chromosomes are found in all major taxa, and their characteristics, function, and evolution are not yet completely understood. Known as B chromosomes, they are additional and dispensable genetic material that are present in particular individuals of certain populations of some species. In this work, we present the occurrence of B chromosomes in the cichlid Crenicichla lepidota from southern Brazil. The analyzed population showed 2 n  = 48 chromosomes, plus 0, 2, 3, or 4 B chromosomes, being variable among metaphases (intraindividual variation). Morphologically, these B chromosomes were variable in size, similarly to the A chromosomes. B chromosomes did not show heterochromatization. Other cytogenetic markers, such as Nucleolar Organizing Region, CMA3/DAPI base-specific dyes, and Fluorescent in situ hybridization with 18S rDNA probe, showed no differences in relation to previous studies with C. lepidota . Although this is the second description of B chromosomes for this species, we highlight the specific features of this population, especially the similarity to A chromosomes, in relation to size, morphology, and heterochromatin accumulation. In summary the B chromosomes described herein are large to small-sized, euchromatic chromosomes, a result that contrasts with that obtained so far for Neotropical cichlids.